Functional characterization of the three mitogen‐activated protein kinase kinases (MAP2Ks) present in the Cryphonectria parasitica genome reveals the necessity of Cpkk1 and Cpkk2, but not Cpkk3, for pathogenesis on chestnut (Castanea spp.). (13th January 2014) - Moretti, Marino; Rossi, Marika; Ciuffo, Marina; Turina, Massimo
Summary The biological function(s) of the cpkk1, cpkk2 and cpkk3 genes, encoding the three mitogen‐activated protein kinase kinases (MAP2Ks) of Cryphonectria parasitica, the causal agent of chestnut blight, were examined through knockout strains. Cpkk1, the Mkk1 orthologue, acts in a phosphorylation cascade essential for cell integrity; Cpkk2 is the Ste7 orthologue involved in the pheromone response pathway; Cpkk3 is the Pbs2 orthologue, the MAP2K activated during the high‐osmolarity response. Our analysis confirmed the role of each MAP2K in its respective signalling cascade with some peculiarities: abnormal hyphae with a reduced number of septa and thinner cell walls were observed in Δcpkk1 mutants, and a strong growth defect on solid media was evident in Δcpkk2 mutants, when compared with the controls. Virulence on chestnut was affected in both the Δcpkk1 and Δcpkk2 strains, which were also unable to complete the developmental steps essential for mating. No alterations were reported in Δcpkk3, except under hyperosmotic conditions and in the presence of fludioxonil. Δcpkk2 mutants, however, showed higher sensitivity during growth in medium containing the antibiotic G418 (Geneticin).